Beam-Column Resistance According to Slovak Standard and Eurocodes - Janik, Peter; Vican, Josef (Communications - Scientific letters of the University of Zilina, 2013)
The article deals with the verification of resistance of torsionally restrained hot-rolled beam-columns of H or I cross-sectional shape and also of the perpendicular hollow cross-section subjected to the biaxial bending and axial compression. Results of analysis of the beam-column resistances according to methods of former STN 73 1401 [1] and the current STN EN 1993-1-1 [2] are compared with results of numerical approaches. The observed members are subjected to the normal force and to the transverse loads uniformly distributed along the length of both axes. The cross-sections of HEB 300, IPE 300 and RHS 300x200x10 were chosen to compare obtained results.